2023
DOI: 10.3390/en16073189
|View full text |Cite
|
Sign up to set email alerts
|

Review on Mono and Hybrid Nanofluids: Preparation, Properties, Investigation, and Applications in IC Engines and Heat Transfer

Abstract: Nano fluids are widely used today for various energy-related applications such as coolants, refrigerants, and fuel additives. New coolants and design modifications are being explored due to renewed interest in improving the working fluid properties of heat exchangers. Several studies have investigated nanofluids to enhance radiator and heat exchanger performance. A new class of coolants includes single, binary, and tertiary nanoparticle-based hybrid nano-coolants using ethylene glycol/deionized water combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(4 citation statements)
references
References 344 publications
0
2
0
Order By: Relevance
“…It has been observed that the viscosity of the sample decreases with an increase in temperature, indicating the significant influence of temperature on its rheological properties. Therefore, it is crucial to carefully consider and control the temperature conditions during the testing and application of the sample to ensure optimal performance and desired outcomes [41]. Rheological experiments were conducted using the Anton Paar MCR 502 rheometer, Montreal, Canada, wherein the apparent viscosity measurements were obtained by varying the shear rate or time at different temperatures according to Equation (5), which shows the relation of the ratio of the shear stress to shear rate to determine the viscosity to evaluate the rheological properties.…”
Section: Frac Fluid Rheology Testmentioning
confidence: 99%
“…It has been observed that the viscosity of the sample decreases with an increase in temperature, indicating the significant influence of temperature on its rheological properties. Therefore, it is crucial to carefully consider and control the temperature conditions during the testing and application of the sample to ensure optimal performance and desired outcomes [41]. Rheological experiments were conducted using the Anton Paar MCR 502 rheometer, Montreal, Canada, wherein the apparent viscosity measurements were obtained by varying the shear rate or time at different temperatures according to Equation (5), which shows the relation of the ratio of the shear stress to shear rate to determine the viscosity to evaluate the rheological properties.…”
Section: Frac Fluid Rheology Testmentioning
confidence: 99%
“…Bhattad et al [5] also proved the thermal capability of hybrid nanofluid in a specific investigation on a plate heat exchanger. A comprehensive review of theoretical and experimental studies conducted on hybrid nanofluid can be found in the review papers written by Vallejo et al [6], Vărdaru et al [7], Bhattad et al [8], Mahdy et al [9], El-Zahar et al [10][11][12], Nabwey et al [13], and in the book by Merkin et al [14].…”
Section: Introductionmentioning
confidence: 99%
“…Obalalu et al ., (2023a) studied hybrid nanofluids with some practical limitation and discusses an applications of hybrid nanofluids in solar energy systems. By incorporating hybrid nanofluids, these systems can potentially achieve higher temperatures and better heat transfer rates, leading to increased overall efficiency (Huminic and Huminic, 2018; Bhattad et al ., 2023; Aglawe et al ., 2021; Tabrez and Azeem Khan, 2022; Gorla and Chamkha, 2011).…”
Section: Introductionmentioning
confidence: 99%